Corporations and Health: The Need to Combine Forces to Improve Population Health - Mélissa Mialon; Gary Fooks; Katherine Cullerton; Clara Gómez-Donoso; Hernando Salcedo Fidalgo; Rima Nakkash; Jennifer Lacy-Nichols (Kerman University of Medical Sciences, 2022)
The recent concerns raised about commercial determinants of health (CDoH) are not new. Numerous organizations around the world are working on these issues. These groups have emerged in response to specific issues and contexts and bring with them a diversity of interests, worldviews and strategies for change. In creating the 'Governance, Ethics and Conflicts of Interest in Public Health' network in 2018, our hope was to broaden our engagement with other actors advocating for change and strengthen our collective efforts. For academics, this requires moving further beyond the collective comfort zone of peer-reviewed publications, working with the media and those with political expertise, and learning from and supporting other stakeholders with a common vision.